Towards automated pre-ingest workflow for bridging information systems and digital preservation services. (18th November 2019) - Westerlund, Parvaneh; Andersson, Ingemar; Päivärinta, Tero; Nilsson, Jörgen
Abstract : Purpose: This paper aims to automate pre-ingest workflow for preserving digital content, such as records, through middleware that integrates potentially many information systems with potentially several alternative digital preservation services. Design/methodology/approach: This design research approach resulted in a design for model- and component-based software for such workflow. A proof-of-concept prototype was implemented and demonstrated in context of a European research project, ForgetIT. Findings: The study identifies design issues of automated pre-ingest for digital preservation while using middleware as a design choice for this purpose. The resulting model and solution suggest functionalities and interaction patterns based on open interface protocols between the source systems of digital content, middleware and digital preservation services. The resulting workflow automates the tasks of fetching digital objects from the source system with metadata extraction, preservation preparation and transfer to a selected preservation service. The proof-of-concept verified that the suggested model for pre-ingest workflow and the suggested component architecture was technologically implementable. Future research and development needs to include new solutions to support context-aware preservation management with increased support for configuring submission agreements as a basis for dynamic automation of pre-ingest and more automated error handling. Originality/value: The paper addresses design issues for middleware as a design choice to support automated pre-ingest in digital preservation. The suggested middleware architecture supports many-to-many relationships between the source information systems and digital preservation services through open interface protocols, thus enabling dynamic digital preservation solutions for records management.